Functional Cyst Aspiration At The Beginning Of ICSI Cycle Does Not Have Detrimental Effect on ICSI Outcomes - İbrahim Esinler; Lale Sökmensüer; Gürkan Bozdağ; Deniz Esinler; Murat Gültekin; Tarık Aksu; Serdar Günalp (Medical Network, 2007)
OBJECTIVE: The aim of our study is to investigate the effect of functional simple cyst aspiration at the beginning of intracytoplasmic sperm injection (ICSI) cycles on controlled ovarian hyperstimulation (COH) and ICSI outcomes. Design retrospective case-control study. STUDY DESIGN: Fifty consecutive patients (69 cycles, Group I) who underwent functional cyst aspiration at the beginning of ICSI cycle were enrolled retrospectively via our computerized IVF database system. The control group was constituted from the 70 patients (99 cycles, tubal factor infertility, Group II). RESULTS: Controlled ovarian hyperstimulation responses, embryological data and pregnancy outcome of both groups were all comparable. CONCLUSION: Functional simple cysts aspiration at the beginning of ICSI cycles does not have detrimental effect on both COH and ICSI outcomes.